A new species of Asphondylia (Diptera: Cecidomyiidae) causing leaf galls on jujube, Ziziphus jujuba Mill. (Rhamnaceae) in India - Vasanthakumar, Duraikannu; Palanisamy, Senthilkumar; Peter, Vinny R.; Sharma, Radheshyam M. (Zootaxa, 2020)
Jujube Ziziphus jujuba Mill. (Rhamnaceae), known as “Ber” in India, is an evergreen thorny shrub with reddish-brown fruits, chiefly found in Southeast Asia (Reza 2014). Up to now three species of gall midges have been associated with jujube: Phyllodiplosis jujubae Grover & Bakshi, and Silvestrina jujubae Chandra in India and Dasineura jujubifolia Jiao & Bu in China (Grover & Bakhshi 1978; Chandra 1988; Jiao et al. 2017). Between 2015 and 2018 during field trips by DV & VRP to Singanallur lake area, Coimbatore, Tamil Nadu, one of us (DV) noticed and collected leaves of Z. jujuba containing small galls on the midrib region of leaves. In the laboratory the leaves were dissected, and causative agent identified as a gall midge. The adults were reared and identified as undescribed species of gall midge, here described and named Asphondylia singanallurensis Vasanthakumar & Sharma. Type specimens were processed and mounted in Canada balsam as per the method in Kolesik et al. (2015). Holotype and paratypes were prepared and deposited in the collection of the Zoological Survey of India, WRC, Pune.